Keterlibatan Ulama dalam Pemenangan Caleg DPRD Provinsi Dapil VI Tahun 2019 (Studi Kasus Desa Sukacinta Kecamatan Sungai Rotan Kabupaten Muara Enim) - Afip, Afip; Rochmiatun, Endang; Adytyas, Nico Oktario (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
this study aims, firstly to determine the interaction of ulama with the government and political figures and second to determine the form of ulama involvement in winning the Regional Legislative Council Candidates for Electoral District VI in Sukacinta Village, Sungai Rotan District, Muara Enim Regency. This research uses a qualitative method where the results of observations and some data related to the research are collected in order to interpret the study as detailed as possible, so that the results of the research are clear that the relationship between ulama and politics is not always caused by economic motives, dependence, or so on. More than that, both of them also stand as two entities that can form contributive and solution partners in practicing the humanist values ​​of Pancasila. Especially the implementation of the fifth principle, namely social justice for all Indonesian people. Therefore, it would not be wiser if scholars and politics were only seen tendentiously and excluded their potentialities which could significantly change the benefit of the people. Keywords: Ulama, Government, Politician